New insights into the reproductive physiology and culture approaches of Paratilapia sp., a Malagasy cichlid with potential interest for sustainable aquaculture - Marta Caballero‐Huertas; Marc Canonne; Domoina Rakotomanana; Rovaniaina Jospin Césaire Tianandriatsiferana; Tsiriniaina Andrianjafisoa; Jean Robertin Rasoloariniaina; Jean‐Michel Mortillaro (Journal of the World Aquaculture Society)
Abstract One of the primary objectives in freshwater aquaculture is the search for sustainable systems based on agroecological intensification. In this context, the cultivation of local species is decisive, although requiring the identification of new candidates. Malagasy aquaculture is an example of the development of such an approach. We aimed to deepen the knowledge of the biology of the Paratilapia sp., specifically, their reproductive traits and zootechnical aspects, with special emphasis on the juvenile stages. The information provided has interest for its commercial production and the species conservation, as populations are subjected to overexploitation and habitat degradation. This study is a consolidated report on morphological characteristics, sexual dimorphism, reproductive biology, and early developmental ontogeny. The main results suggested a marked sexual dimorphism, as well as greater growth of males compared with females. Aggressive behavior between males was observed before pair formation. Generally, female and males provided protection until fry are independent. Females produced 2756 ± 598 eggs per spawn on average (gonadosomatic index = 4.6%), with a reproductive frequency of one to two spawns. Despite the need to improve breeding protocols, this work represents a breakthrough in producing a local freshwater species of potential interest.